2018
DOI: 10.3389/fphar.2018.01431
|View full text |Cite
|
Sign up to set email alerts
|

TAK-442, a Direct Factor Xa Inhibitor, Inhibits Monocyte Chemoattractant Protein 1 Production in Endothelial Cells via Involvement of Protease-Activated Receptor 1

Abstract: Oral blood coagulation inhibitors and their receptors, such as factor Xa (FXa), thrombin, and the thrombin receptor protease-activated receptor 1 (PAR1), are entered into clinical trials for acute coronary syndrome therapy; however, the results obtained so far are different for each drug. The underlying mechanisms of the results have not been fully investigated. We studied the in vitro anti-inflammatory effects of the selective FXa inhibitor TAK-442 on human endothelial cells, with comparing those of the selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…As shown in Figure A,B, P-2-CG (0.1 mM) and thrombin (1 U) had no discernible influence on HUVECs viability ( p > 0.05). This finding was consistent with previous results. − The disrupted ECs also expressed a variety of physiological/pathological factors (such as ROS, cytokines, and vWF). , Furthermore, these factors trigger platelet aggregation and induce thrombosis further. Exposure of HUVECs to thrombin resulted in an enhanced release of inflammatory molecule IL-6 (Figure C) and prothrombotic agent vWF (Figure D).…”
Section: Resultssupporting
confidence: 93%
“…As shown in Figure A,B, P-2-CG (0.1 mM) and thrombin (1 U) had no discernible influence on HUVECs viability ( p > 0.05). This finding was consistent with previous results. − The disrupted ECs also expressed a variety of physiological/pathological factors (such as ROS, cytokines, and vWF). , Furthermore, these factors trigger platelet aggregation and induce thrombosis further. Exposure of HUVECs to thrombin resulted in an enhanced release of inflammatory molecule IL-6 (Figure C) and prothrombotic agent vWF (Figure D).…”
Section: Resultssupporting
confidence: 93%
“…In fact, FXa was found to stimulate proinflammatory and profibrotic responses in fibroblasts [58], human atrial tissue [59], and RAW 264.7 macrophages [60] via protease-activated receptor-2. An investigational FXa inhibitor was also recently reported to inhibit MCP-1 production in endothelial cells via protease-activated receptor-1 [61]. As a result, FXa-mediated signaling has been implicated in the pathogenesis of several inflammatory diseases, including fibrosis, cardiovascular diseases, diabetic nephropathy, and cancer [62,63].…”
Section: Anti-inflammatory Activity Of Direct Fxa Inhibitorsmentioning
confidence: 99%
“…Thus, PAR1 has been shown to be expressed in activated ECs of atherosclerotic plaque, but not in non-diseased cardiac arteries [ 15 , 16 , 41 ]. Previous studies demonstrated that vorapaxar prevented endothelial barrier disruption in cultured ECs [ 42 , 43 , 44 , 45 ]. Here, we report that vorapaxar reduced the expression of inflammation-associated adhesion molecules and TF, both in isolated ECs and the aorta in a murine model of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%